Trypanosomatid, fluorescence-based in vitro U-insertion/U-deletion RNA-editing (FIDE) - Leeder, Wolf-Matthias (Bio-Protocol, 2021)

(untitled) (Bio Protoc)
Gene expression within the mitochondria of African trypanosomes and other protozoan organisms relies on a nucleotide-specific RNA-editing reaction. In the process exclusively uridine (U)-nucleotides are site-specifically inserted into and deleted from sequence-deficient primary transcripts to convert them into translatable mRNAs. The reaction is catalyzed by a 0.8 MDa multiprotein complex termed the editosome. Here we describe an improved in vitro test to quantitatively explore the catalytic activity of the editosome. The assay uses synthetic, fluorophore-derivatized oligoribonucleotides as editing substrates, which enable the automated electrophoretic separation of the reaction products by capillary electrophoresis (CE) coupled to laser-induced fluorescence (LIF) detection systems. The assay is robust, it requires only nanogram amounts of materials and by using multicapillary CE/LIF-instruments it can be executed in a highly parallel layout. Further improvements include the usage of phosphorothioate-modified and thus RNase-resistant substrate RNAs as well as multiplex-type fluorophore labeling strategies to monitor the U-insertion and U-deletion reaction simultaneously. The assay is useful for investigating the mechanism and enzymology of the editosome. However, it can also be executed in high-throughput to screen for RNA editing-specific inhibitors. Graphic abstract: [Image: see text] Characteristics of the fluorescence-based in vitro U-insertion/U-deletion RNA-editing (FIDE) assay